Laporan Keuangan Menggunakan Aplikasi SIAPIK Bagi UMKM Oti Mbootz - Ferica Christinawati Putri (CV. Multi Kreasi Media, 2022)
Along with the development of information technology, the current preparation of financial reports can be done in a practical way by using an application on a smartphone, namely the SiAPIK application. SiAPIK provides convenience in terms of recording every transaction and producing financial reports in the form of Balance Sheets, Changes in Capital, and Profit and Loss Reports. This activity aims to provide assistance in using the SiAPIK Application to produce financial reports for one of the MSMEs in Tarakan City, namely Oti Mbootz. The method used in this community service activity consists of outreach and assistance in preparing financial reports using the SIAPIK application. The result of this community service activity is an increase in the knowledge of business owners regarding the importance of preparing financial reports for business operations and an increase in the ability to record transactions that can produce financial reports in the form of a Balance Sheet, Profit and Loss Statement.